Pengaruh Kualitas Pelayanan, Harga dan Store Atmosphere terhadap Kepuasan Konsumen (Studi pada konsumen Cokelat Klasik Cafe & Garden Sulfat Malang) - Riki Setiawan; Rusno Rusno; Iva Nurdiana Nurfarida (Jurnal Riset Mahasiswa Manajemen, 2018)
This study to determine the effect of service quality, price and store atmosphere on consumer satisfaction (studies on consumers of classic chocolate cafÃ© & Garden Sulfate Malang). This study uses quantitative research with an explanatory research type with consumers population of Classic Chocolate Cafe & Garden, with as many samples 102 consumers, data collection techniques using a questionnaire with a purposive sampling method, data analysis techniques using multiple linear regression analysis. The results of the analysis show that service quality, price and store atmosphere simultaneously influence customer satisfaction, service quality partially significantly influences customer satisfaction, price partially has a significant effect on customer satisfaction, store atmosphere partially has insignificant effect on customer satisfaction.